1992
DOI: 10.1159/000118835
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Four-Hour Beta-Endorphin Secretory Pattern in Alzheimer’s Disease

Abstract: A chronobiological study was carried out in 6 male patients (67–71 years), suffering from Alzheimer-type dementia (ATD) and 6 male patients (52–74 years) suffering from multi-infarct dementia (MID), to evaluate their 24-hour β-endorphin and cortisol secretory patterns. Six healthy male adults (28–37 years) and 6 healthy elderly male subjects (78–84 years) constituted the control groups. Blood samples were drawn every 4 h from 8.00 to 20.00 h and every 2 h from 24.00 to 6.00 h. Mean 24-hour β-endorphin levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Previous evidence regarding the differences in neuroendocrine function between AD and VD patients indicated contrasting results: while neuroendocrine regulation of growth hormone (GH) appeared more damaged in AD than in multi-infarct dementia patients (40), both AD and VD patients showed a similar behavior of plasma b-endorphin and cortisol circadian rhythms and similar abnormalities of dexamethasone suppression test (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence regarding the differences in neuroendocrine function between AD and VD patients indicated contrasting results: while neuroendocrine regulation of growth hormone (GH) appeared more damaged in AD than in multi-infarct dementia patients (40), both AD and VD patients showed a similar behavior of plasma b-endorphin and cortisol circadian rhythms and similar abnormalities of dexamethasone suppression test (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…The recent observation [Scherder and Bouma, 2000] that AD patients complain more of acute than chronic pain reinforces the idea of a delay in pain report because of a loss of past points of reference. These changing states of memory probably involve much more than muscarinic cholinergic and NMDA systems, as different degrees of impairment in a variety of other neurotransmitter systems like benzodiazepine and serotoninergic [Cain et al, 2000] and endogenous opioid systems [Rolandi et al, 1992] have been observed in AD. Recent evidence has also shown that the central muscarinic and the NMDA systems interact in the hippocampus in the modulation of cognitive function [Li et al, 1997[Li et al, , 2001Daniel and Dohanich, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…A link between the /3-endorphin secretory pattern and functional outcome cannot be established with certainty by our study because of the relatively small number of cases. However, if we consider that similar changes in the /3-endorphin secretory pattern occur in multi-infarct dementia, 23 the possibility that /3-endorphin secretion might potentially serve as a marker of motor, cognitive, and behavioral function after stroke may be proposed.…”
Section: Discussionmentioning
confidence: 99%